Evaluation of Topographic Mapping Possibilities from Cartosat High Resolution Data - Baral, Govinda Prasad; Karki, Sudarshan; Kayastha, Durgendra Man (Journal on Geoinformatics, Nepal, 2007)
Re-surveying or mapping is usually required when user needs for up-to-date maps at various scales are not met by existing maps. Generally, the requirements are for large scale mapping and the outputs may be in digital format or hardcopy or both. Data acquisition may be from field survey, aerial photographs or satellite imagery. Nowadays, due to availability of high resolution satellite imageries, scales 1:2,500 to 1:10,000 can be mapped for large areas as an alternative to field survey. Cartosat is producing stereo satellite imageries of 2.5m spatial resolution. This paper evaluates the possibilities of mapping at 1:10,000 from this Cartosat image. Evaluation of accuracy is done for both planimetric and height mapping. Also the optimum scales that can be derived from the Cartosat stereo-pair are suggested.